Constitutional Foundations of Activity of Non-Commercial Organizations on Making of Public Goods - N. V. Razuvaev (Теоретическая и прикладная юриспруденция)
The basic human needs include the need for public goods, which are met by the Constitution of the Russian Federation. The State cannot be the sole producer of such goods, as the state monopoly in the public sector has a negative impact on the quality of public goods. Their production should be based on the competitive activities of non-commercial organizations (NCO). The participation of the state and local governments in the public sector should be limited primarily to financing the expenditure of citizens on the consumption of public goods, as well as to the regulation and control of the activities of NCO.The constitutional basis for the creation of NCO, based on membership is the right to union, guaranteed art. 30 of Constitution of the Russian Federation. Creating conditions for the realization of the right of citizens to unite requires a system of guarantees, which includes socio-economic, political, legislative and other guarantees. A special role among the guarantees of the right of citizens to unite is played by its judicial protection against the misconduct of the state and local government. Such protection should be directed at the application of liability measures to public entities, their bodies and officials in the event of violations of the rights and legitimate interests of non-profit organizations or their members.